A Message in the Almighty’s Saying (The Adulterer does not Marry Except an Adulteress or a Polytheist) by Imam Sarri Al-Din Al-Dururi, Known as Ibn Al-Sayegh, who died aRound the Year 1066 AH - Study and Verification - (Islamic Sciences Journal, 2023)
ABSTRACT                        Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and all his family and companions. The science of interpretation is one of the most important sciences of Sharia because it is related to the Book of Allah Almighty, as it is the first resource from which scholars draw their opinions in various other legal sciences. No nation has served a book as masked Muslims have served the book of their Lord Almighty, and the service of this book is still continuing and will continue to continue and what is this  except for another aspect of the miraculousness of the Noble Qur’an, for what was hidden from an interpreter appeared to another interpreter, and what was confused with an interpreter of indicated for another, To serve the Book of Allah Almighty is to serve what the previous scholars wrote in its interpretation, which may be large interpretations, or short messages Or other books on the science of interpretation, so we verify it and show it to students of knowledge and enrich the Islamic library with it. Among these works is a message in the Almighty’s saying: (The adulterer does not marry except an adulteress or a polytheist) by Imam Sari al-Din al-Dururi, known as Ibn al-Sayegh, who died around the year 1066 AH, which was the project of our humble research, so we ask him Allah Almighty grants success, acceptance and payment, for He is the Guardian of that and the One who is able to do so.